ADVANCES IN COMPUTER TECHNOLOGY: FROM MECHANICS TO ARTIFICIAL INTELLIGENCE - Muhammad Ridho Ardiansyah; Ibnu Aqil, Irwansyah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The development of computer technology has undergone a significant evolution from the outset as a mechanical tool for calculating and storing data into systems capable of performing tasks with artificial intelligence. Digitization of data and processes has driven efficiency in various aspects of life, while the development of artificial intelligence enables machines to learn, adapt, and perform tasks that normally require human intelligence. The research method in this research is the study of literature by finding the theory in accordance with the context of penalty. The results of this research reveal that the development of computer technology has driven major innovations in a variety of fields, including industrial automation, development of autonomous cars, and the application of artificial intelligence in health. However, while these developments bring positive benefits such as improved efficiency and ease of access to information, there are also new challenges such as concerns about privacy and the impact of artificial intelligence on everyday life. The development of computer technology continues, and in the future we will probably see more innovations that will affect the way we live and work. It is therefore important to ensure that these developments are managed wisely, considering their impact on society and finding the right balance between technological progress and the general interest.